Analisis Pengaruh Penggunaan Canva Terhadap Kreativitas Mahasiswa PBSI pada Mata Kuliah Penulisan Modul - Lase, Julita Hertawati; Gea, Lince Imerda; Telaumbanua, Kalvin Septianus; Ndruru, Mastawati (Indo-MathEdu Intellectuals Journal, 2024)
Information technology in the digital age has become an important component in education, offering a variety of digital tools that can improve the quality of learning. One popular tool is Canva, a graphic design platform that makes it easy to create engaging and creative learning materials. This research focuses on the use of Canva in module writing courses at the Indonesian Language and Literature Education Study Program at the University of Nias. This study uses a qualitative approach with a descriptive method. The research instruments include module drafts, interview sheets, observation sheets. Data analysis is carried out through data reduction, presentation of data in the form of tables, and drawing valid and consistent conclusions. The results of the analysis show that Canva's features, such as templates and graphic elements, support the process of visualizing and organizing information, and increase student motivation and engagement in the learning process